2018
DOI: 10.1002/hbm.24420
|View full text |Cite
|
Sign up to set email alerts
|

Brain state and polarity dependent modulation of brain networks by transcranial direct current stimulation

Abstract: Despite its widespread use in cognitive studies, there is still limited understanding of whether and how transcranial direct current stimulation (tDCS) modulates brain network function. To clarify its physiological effects, we assessed brain network function using functional magnetic resonance imaging (fMRI) simultaneously acquired during tDCS stimulation. Cognitive state was manipulated by having subjects perform a Choice Reaction Task or being at “rest.” A novel factorial design was used to assess the effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 113 publications
(101 citation statements)
references
References 84 publications
6
87
0
Order By: Relevance
“…The study protocol is selected based on several assumptions and hypotheses such as time course of tDCS effect (Nitsche & Paulus, ), cellular mechanism of stimulation (Bikson et al, ; Rahman et al, ), state dependency of tDCS as a subthreshold stimulation method (Hsu, Juan, & Tseng, ; Li et al, ), and dose–response relationship. Ultimately, these considerations get to the heart of how tDCS research benefits from functional MR imaging and how to address inherent challenges in experimental design.…”
Section: Tdcs‐mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
See 2 more Smart Citations
“…The study protocol is selected based on several assumptions and hypotheses such as time course of tDCS effect (Nitsche & Paulus, ), cellular mechanism of stimulation (Bikson et al, ; Rahman et al, ), state dependency of tDCS as a subthreshold stimulation method (Hsu, Juan, & Tseng, ; Li et al, ), and dose–response relationship. Ultimately, these considerations get to the heart of how tDCS research benefits from functional MR imaging and how to address inherent challenges in experimental design.…”
Section: Tdcs‐mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
“…In contrast, resting‐state fMRI is a technique performed in wakefulness without a superimposed task to execute. If the nature of tDCS is (profoundly) influenced by brain state (Li et al, ; Shahbabaie et al, ), stimulation of different individuals with same current flow profile could lead to different results based on their brain state. In studies where both resting‐state and task‐fMRI is acquired the order of imaging is important meaning if rs‐fMRI is performed after task‐fMRI, the former may affect network activity during the latter (i.e., “brain state” change).…”
Section: Tdcs‐mr Imaging: Trial Design Parameter Spacementioning
confidence: 99%
See 1 more Smart Citation
“…because effect could be driven by other incidentally affected brain regions." Both tDCS and TMS are shown to initiate these "unintended" effects: Bestmann showed using MRI that TMS of motor cortex below the threshold power can activate some other deeper structures, contrary to previous belief and Li showed similar phenomena in the case of tDCS (Bestmann et al, 2003(Bestmann et al, , 2004Li et al, 2018).…”
Section: Introductionmentioning
confidence: 79%
“…Bestmann et al (2004) demonstrated that with TMS application below the motor threshold power, MRI can detect a response from areas that were not intended to be stimulated (Bestmann et al, 2004). Li et al (2018) were the first research group to demonstrate that tDCS can activate some structures within DMN. Opitz et al (2015) conclude in their work that even the conductivity constants (dielectric constants for tissue types) used for calculating the effect of stimulation, or simulation, are not adequate for describing the much more demanding reality.…”
Section: Introductionmentioning
confidence: 99%